Integrating English Games to Enhance Intrinsic Motivation in Young Learners’ Classroom - Asliati, Asliati; Harahap, Rilyani; Nurliyandi; Mutiara Dewi, Cut; Diana, Sari (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This study investigated students’ perception of the integrating English games to strengthen intrinsic motivation among young English learners in West Aceh. Using a mixed-methods sequential explanatory design, quantitative data were collected through a questionnaire administered to 27 fifth-grade students at SD Negeri 12 Meulaboh, followed by semi-structured interviews with six participants. The findings indicated that, in term of enjoyment, 100% of students reported that learning English through games was enjoyable and helped them understand the lessons more easily, while 92.5% felt more confident and motivated during the activities. Regarding interest, students showed strong engagement, with all respondents stating that games increased their focus, and over 96% agreeing that games reduced boredom and improved their confidence in responding to teachers’ questions. The results also demonstrate a strong desire to continue learning English using games, as 100% agreed that games increased their liking for English, and more than 96% hoped for similar activities in future lessons. Additionally, students displayed high enthusiasm, with 96.2% feeling closer to their peers and more motivated to continue learning English, while 92.5% stated that games boosted their courage to speak without fear of mistakes.